Evaluation of the Healthy Families New York Home Visiting Program, Age Seven Follow Up, 2007-2009 - DuMont, Kimberly ([Verlag nicht ermittelbar], 2012)
Healthy Families New York (HFNY), which was based on the Healthy Families America (HFA) model, was established as a strengths-based, intensive home visitation program with the explicit goals of promoting positive parenting skills and parent-child interaction; preventing child abuse and neglect; supporting optimal prenatal care, and child health and development; and improving parent's self-sufficiency.In 2000, a randomized controlled trial was initiated at three sites with the HFNY home visiting program. Families eligible for HFNY at each site were randomly assigned to either an intervention group that was offered HFNY services or to a control group that was given information on and referral to appropriate services other than home visiting. Baseline interviews were conducted with 1,173 of the eligible women (intervention, n=579; control, n=594), and follow up interviews at Years 1, 2, and 3. In addition to data gathered during the follow up interviews, information regarding study participants' involvement in reports of child maltreatment was also extracted and coded from Child Protection Services records.For the current study, mothers in both the intervention and control groups were re-interviewed at the time of the target child's seventh birthday. Interviews (Dataset 1: Mother Interview Data, n=942) included information about parenting, the child, earnings, and household composition. Interviewers also completed face-to-face assessments (Dataset 2: Target Child Interview Data) with 800 of the children who were born and reached the age of 7 at the time of interview. The target child interviews assessed children's receptive vocabulary skills, emotional health, self-regulatory abilities, and problem behaviors. The research team also extracted or obtained administrative data pertaining to Child Protective Service reports, foster care placements, federal and state supported benefits, and programs services and costs (Datasets 3-8).